-1
$\begingroup$

If $v = Ve^{-j(wt+A)}, i= Ie^{-j(wt+B)}$ then show that the impedance $z = v/i$ is given by $$Z = (V/I)\cdot[\cos(A-B) + j\sin(A-B)]$$

I get confused because when I used the correct rules, it always comes to $$(V/I)\cdot[\cos(A-B) - j\sin(A-B)]$$ instead because of the rule that $e^{-j(\theta)}=\cos(\theta) - \sin(\theta)$

$\endgroup$
  • $\begingroup$ If $j=\sqrt{-1}$, your answer is correct (although you might want to check the rule $e^{-j(\theta)}=\cos(\theta) - \sin(\theta)$ again) $\endgroup$ – Shubham Johri Dec 16 '18 at 10:30
0
$\begingroup$

Well,

$$ \frac{v}{i} = \frac{V}{I}e^{-j(A-B)} = \frac{V}{I} [\cos(-(A-B))+j\sin(-(A-B))]$$ by Euler's formula, then because cosine is even and sine is odd, $$ \frac{v}{i} = \frac{V}{I} [\cos(A-B) -j \sin(A-B)].$$

You got it

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.